Myxedema Coma: A Life-Threatening Condition in Patients Using Pembrolizumab - Sangeetha Gummalla; Madhura Manjunath; Brian Phillips (Case Reports in Endocrinology)
The advent of immune checkpoint inhibitors has significantly improved the prognosis of patients with advanced malignancies. As we begin to understand these medications, multiple immune-related adverse effects (irAEs) have been found with these drugs, including endocrinopathies. Understanding the treatment-related adverse events of these medications is critical for clinical practice. Thyroid-related adverse effects usually occur within the first three months of treatment and rarely after eight months. It can manifest as an early onset of thyrotoxicosis, which is largely asymptomatic, followed by a rapid transition to hypothyroidism, requiring long-term levothyroxine substitution. We present a case in which our patient was found unresponsive, hypothermic, and with respiratory failure almost after completing a year of treatment with pembrolizumab. He had an initial mild elevation in thyroid-stimulating hormone (TSH) of 6.52, although with normal free thyroxine (T4) of 1.06, in his first three months of starting treatment which then rapidly progressed to a true myxedema coma. The infrequency with which this occurs makes it a diagnostic challenge.